Acute effects of postural changes and lower body positive and negative pressure on the eye - Van Akin, M. P.; Lantz, O. M.; Fellows, A. M.; Toutain-Kidd, Christine; Zegans, Michael; Buckey, J. C.; Anderson, A. P. (Frontiers in Physiology, 2022)
Introduction: Entry into weightlessness results in a fluid shift and a loss of hydrostatic gradients. These factors are believed to affect the eye and contribute to the ocular changes that occur in space. We measured eye parameters during fluid shifts produced by lower body negative pressure (LBNP) and lower body positive pressure (LBPP) and changes in hydrostatic gradient direction (supine-prone) in normal subjects to assess the relative effects of fluid shifts and hydrostatic gradient changes on the eye. Methods: Ocular parameters (intraocular pressure (IOP), ocular geometry, and optical coherence tomography measures) were measured in the seated, supine, and prone positions. To create a fluid shift in the supine and prone positions, the lower body chamber pressure ranged from -40 mmHg to +40 mmHg. Subjects maintained each posture and LBNP/LBPP combination for 15 minutes prior to data collection. A linear mixed-effects model was used to determine the effects of fluid shifts (as reflected by LBNP/LBPP) and hydrostatic gradient changes (as reflected by the change from seated to supine and from seated to prone) on eye parameters. Results: Chamber pressure was positively correlated with both increased choroidal thickness (β = 0.11, p=0.01) and IOP (β = 0.06 p<0.001). The change in posture increased IOP compared to seated IOP (supine β = 2.1, p=0.01, prone β = 9.5, p<0.001 prone) but not choroidal thickness. IOP changes correlated with axial length (R = 0.72, p<0.001). Discussion: The effects of hydrostatic gradients and fluids shifts on the eye were investigated by inducing a fluid shift in both the supine and prone postures. Both hydrostatic gradients (posture) and fluid shifts (chamber pressure) affected IOP, but only hydrostatic gradients affected axial length and aqueous depth. Changes in choroidal thickness were only significant for the fluid shifts. Changes in hydrostatic gradients can produce significant changes in both IOP and axial length. Fluid shifts are often cited as important factors in the pathophysiology of SANS, but the local loss of hydrostatic gradients in the head may also play an important role in these ocular findings.